THE EFFECT OF LEARNING PROBLEM BASED LEARNING (PBL) AND TASK BASED LEARNING (TBL) LEARNING MODELS AND LEARNING STYLE TO SKILL WRITING NARRATION - Ali, Muhammad; Emzir, Emzir; Rafli, Zainal (IJLECR (International Journal of Language Education and Cultural Review), 2017)
The purpose of this research to examine the influence of learning models and learning styles to the skills of writing narrative essay students of the second semester of the Indonesian Language Studies Program University PGRI Palembang. This research used experimental method with two way ANAVA design with level of Î± = 0,05. This study shows the result that; (1) Student narrative writing skills taught by PBL models are better than those taught by the TBL model, (2) Student narrative writing skill with FI learning style is better than those who study with FD learning style, (3) interaction Between learning models, learning styles, and narrative writing skills, (4) The results of the writing skills of students who have Field Independent learning styles and learning styles with PBL learning models are better than their narrative writing skills that have Field Independent learning styles and learning with learning models TBL, (5) The result of students writing skill with Field Dependent learning style and learning with PBL learning model is not better than their learning style having Field Dependent learning style and learning TBL learning model. Based on the results of the study it can be concluded that the PBL learning model is more effective than the learning model of TBL in learning narrative writing skills. Learning styles can also influence narrative writing skills because of the interaction between learning models, learning styles and narrative writing skills.